St. Joseph and the Practice of Midwifery in the Nativity: Identifying Gestures of a Midwife Saint - Pires de Almeida, Francisca (Eikón / Imago, 2015)
This article focuses on the representation of St. Joseph in Gregório Lopes’s Nativity (c. 1527) and also on Flemish Nativities of the late Middle Ages and the Early Modern Ages. My initial purpose was to investigate a particular aspect of the figuration of the Saint, portrayed holding a white cloth, cooking or pouring water into a wooden bowl. Recent research claims that the aim of these images was to give motherly attributes to St. Joseph. Still, was this the real intention of painters and comissioners? I believe, based on gestures and attitudes attributed to Christ’s putative father, to be in the presence of moments of midwifery. Taking this point of view also meant that I had to research what were the phases of postpartum rituals.